Reversal of cigarette smoke extract‐induced sinonasal epithelial cell barrier dysfunction through Nrf2 Activation. Issue 11 (31st August 2016) - Tharakan, Anuj; Halderman, Ashleigh A.; Lane, Andrew P.; Biswal, Shyam; Ramanathan, Murugappan
Abstract : Background: Environmental factors such as inhaled pollutants like cigarette smoke may play a significant role in diseases of the upper airway including chronic rhinosinusitis (CRS). Recent studies have shown that cigarette smoke causes impaired airway epithelial cell barrier function likely through environmental oxidative stress related pathways. The purpose of this study is to explore whether enhancing nuclear factor erythroid 2 [NF‐E2]‐related factor 2 [Nrf2], the body's master antioxidant system, can ameliorate cigarette smoke–induced sinonasal epithelial cell (SNEC) barrier dysfunction. Methods: Human SNECs (HSNECs) were grown from control patients at the air‐liquid interface (ALI). HSNECs were stimulated with cigarette smoke extract (CSE) with and without pharmacologic activation of Nrf2. HSNECs were then stained for the epithelial cell junctional proteins zonula occludens 1 (ZO‐1) and junctional adhesion molecule A (JAM‐A) using confocal microscopy. In addition, transepithelial electrical resistance (TER) was measured in cultures before and after stimulation with CSE. Results: CSE stimulation caused a global disruption of the epithelial junctional proteins ZO‐1 and JAM‐A along with an associated decrease in TER levels. Enhancing Nrf2 levels prior to stimulation with CSE was associated with increased localization of ZO‐1 and JAM‐A levels at the cell surface and statistically significant increases in TER levels. Conclusion: This is the first study to demonstrate that cigarette smoke induced SNEC barrier dysfunction is reversible by Nrf2 activation. The Nrf2 antioxidant pathway may represent a potential therapeutic target for cigarette smoke–associated sinonasal inflammation.